Knowledge, Attitude, Practice, and Perceptions of Healthcare Professionals and Community Members Regarding Rabies Control; A Cross-sectional Study - Khatir, Iraj Goli; Mohammad Rahimi; Mudgal, Shiv Kumar; Patidar, Vipin; Kaur, Haneet; Hosseini Marznaki, Zohreh; Fatemeh keshavarzi; Hosseininejad, Seyed Mohammad (Archives of Academic Emergency Medicine, 2026)
Introduction: Despite effective vaccines and post-exposure prophylaxis (PEP), gaps in awareness and practices hinder Rabies control efforts. This study assessed knowledge, attitudes, practices, and perception of healthcare professionals and community members regarding rabies control. Methods: A cross-sectional study was conducted from May 2024 to April 2025 among community people who presented to emergency department (ED) with animal bite and health care professionals who were working in EDs of 4 Hospitals in Sari, Iran. Data were collected using validated questionnaires and analysed with descriptive and inferential statistics. The correlation between studied variables and knowledge, attitudes, practices, and perception of healthcare professionals and community members regarding rabies control were evaluated. Results: 766 participants (383 healthcare professionals, 383 community members) were included. Community knowledge was low, with only 20.1% aware that animal bites can transmit rabies, compared to 98.7% of healthcare workers. Awareness of wound washing with soap and water was inadequate (31.3% among community members; 61.1% among healthcare professionals). Misconceptions about rabies hosts were common. A minority in both groups still relied on traditional healers, delaying appropriate care. Education, pet ownership, and access to clinics were positively correlated with higher knowledge, attitude and practice (KAP) scores. Conclusions: The study found significant shortcomings among healthcare professionals as well as severe gaps in rabies-related knowledge and essential preventive behaviors, especially among community members. Inadequate wound-washing techniques and a lack of knowledge about the routes of transmission underscore the critical need for focused education and ongoing professional training to enhance rabies control.